1979
DOI: 10.1007/bf00350589
|View full text |Cite
|
Sign up to set email alerts
|

Osgood-Schlatter's disease, an emphasis on soft tissue changes in roentgen diagnosis

Abstract: Osgood-Schlatter's disease is a well known entity affecting the adolescent knee. Radiologic examination of the knee has been an integral part of the diagnosis of this condition for decades. However, the soft tissue changes have not been appreciated sufficiently. Emphasis is placed on the use of optimum radiographic technique and xeroradiography in the examination of the soft tissues of the knee.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 3 publications
1
5
0
Order By: Relevance
“…It is known that lowering the photon energy can be used to clarify details of soft tissues. The results are essentially similar to increasing contrast in the evaluation of a digital radiograph, which has been used in the past to assess patients with Achilles tendon problems (Fischer 1974a,b, Scotti et al 1979). …”
Section: Discussionsupporting
confidence: 66%
“…It is known that lowering the photon energy can be used to clarify details of soft tissues. The results are essentially similar to increasing contrast in the evaluation of a digital radiograph, which has been used in the past to assess patients with Achilles tendon problems (Fischer 1974a,b, Scotti et al 1979). …”
Section: Discussionsupporting
confidence: 66%
“…Of the 40 studies included, 25 studies reported on OSD‐related imaging findings 4‐7,9,11‐30 . Most studies used radiography (n = 10) or US (n = 6), with the remaining studies using radiography and US (n = 4), radiography and MRI (n = 3), MRI only (n = 1) and one study using both CT, MRI, radiography, and bone scintigraphy (n = 1).…”
Section: Resultsmentioning
confidence: 99%
“…Some believe the cause to be trauma to the patellar tendon at its insertion to the tibial tubercle (Fig 26) (29,30). Osgood-Schlatter disease is typically seen in active adolescents, particularly those who participate in sports that require jumping, squatting, and kicking, and can be bilateral in up to 50% of patients (30,31).…”
Section: S S S S S Knee Injuriesmentioning
confidence: 99%
“…When used, radiography shows fragmentation of the tibial tubercle, although this finding alone may represent a normal ossification center. Therefore, the most important diagnostic criteria are seen at MR imaging and include (a) soft-tissue swelling anterior to the tibial tuberosity, (b) loss of the sharp inferior angle of the infrapatellar fat pad and surrounding soft tissues, (c) thickening and edema of the inferior patellar tendon, and (d) infrapatellar bursitis (5,29,31). On occasion, the disease along with associated radiographic findings persist into adulthood.…”
mentioning
confidence: 99%